1982
DOI: 10.1055/s-2008-1026054
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Training with Eccentric Muscle Contractions on Exercise Performance, Energy Expenditure, and Body Temperature*

Abstract: To study the effects of exercise training with eccentric muscle contractions on body temperatures, energy cost, and performance capacity, six human subjects were tested before and after a 5-week training program of eccentric exercise. Exercise was performed as leg cycling on a motor-driven ergometer at power levels ranging 252-316 W. Training consisted of three sessions/week for 1 h/session. As a result of the training, VO2, fH, and mean skin temperature were lowered for each subject at the same absolute exerc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0
1

Year Published

1983
1983
2008
2008

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(12 citation statements)
references
References 12 publications
0
11
0
1
Order By: Relevance
“…He suggested that when the level ofexertion is below 50% ofmaximum oxygen consumption, as it is in this study (figure 3), the relative contribution of ventilation to RPE is limited, and the contribution of oxygen consumption is proportional to the percentage of maximal oxygen consumption employed to accomplish the takk. Robertson's model is well supported in the literature (Pandolf 1982) for unloaded locomotion and bicycle ergometry. However, when the effects of load carriage, at both speeds, are expressed as an increment above rest levels along the range from rest to maximum (table 3), it is immediately clear that perceptions of exertion do not increase proportionately with oxygen consumption as the load carried increases.…”
Section: Resultsmentioning
confidence: 70%
See 1 more Smart Citation
“…He suggested that when the level ofexertion is below 50% ofmaximum oxygen consumption, as it is in this study (figure 3), the relative contribution of ventilation to RPE is limited, and the contribution of oxygen consumption is proportional to the percentage of maximal oxygen consumption employed to accomplish the takk. Robertson's model is well supported in the literature (Pandolf 1982) for unloaded locomotion and bicycle ergometry. However, when the effects of load carriage, at both speeds, are expressed as an increment above rest levels along the range from rest to maximum (table 3), it is immediately clear that perceptions of exertion do not increase proportionately with oxygen consumption as the load carried increases.…”
Section: Resultsmentioning
confidence: 70%
“…One factor could dominate the overall rating, it was felt, if it became accentuated by elevated rate, concentration or value. Recent reviews of work in this field (Mihevic 1981, Pandolf 1982,1983 have indicated strong support for the influence of local factors, and cited increasing evidence that central factors do not play as important a role in the perception of exertion as was originally thought. Robertson's model (1982) suggests that although central factors play a role (and relative oxygen consumption a proportional one) in determining the perception of exertion, local factors such as force and rate of muscular contractions, and joint sensations, dominate the RPE.…”
Section: Inboductionmentioning
confidence: 99%
“…However, contrasting with studies where very high ambient temperature rapidly raises core temperature above that registered in control conditions (Gonza´lez-Alonso et al 1999), other studies show that higher perceived exertion is not necessarily accompanied by higher core temperature (Galloway and Maughan 1997;Knuttgen et al 1982;Pitsiladis and Maughan 1999), suggesting that factors such as skin temperature may be particularly important in affecting perceived exertion. Skin temperature responds rapidly to changes in environmental temperature and it is likely that skin temperature has an important effect on modulating the role of core temperature in the perception of exertion.…”
Section: Fig 3 Graphs Depict Values Formentioning
confidence: 74%
“…Given the mechanical characteristics of lengthening actions (i.e., mechanical energy is stored as heat in the working muscles), some studies have reported increases in core temperature during eccentric training (0.7 C) as compared to concentric training. 76 Although other studies did not find such physiologic responses, 77 the potential adverse effects of increased temperature on the thermoregulatory system during eccentric work should be considered in patients with altered cardiorespiratory function. 78 Given the importance of maintaining muscle oxidative potential while reducing cardiopulmonary stress in such patients, these aspects should be addressed in future studies.…”
Section: Cardiorespiratory Diseasesmentioning
confidence: 95%